A critical Study on the Book: The Interpretation of the Civil Code Documents, Judgements and Legal Views - Hossein Qashqaee (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
A critical study on works that have scientific content will lead to the growth and development in a field of knowledge. Having a right understanding of legal articles depends on referring to the original texts from those laws that have been enacted. One major shortcoming of this book is that only some minor religious sources were pointed out to interpret a legal article, while to review a legal article, it is essential to see all the documents and resources, or all legal reasons should be investigated. At least, well-known fatwas available at the time of the law must be examined because it can be considerably helpful. Foundations and presuppositions of any legal article are appropriate with a legal system, and for the interpretation of every legal article, the special legal system should be considered and examined.